Phytoremediation as phytotechnology approach for wastewater treatment : an Islamic perspectives - Farah Ayuni Mohd Hatta,; Qurratu Aini Mat Ali,; Rashidi Othman,; Razanah Ramya,; Wan Syibrah Hanisah Wan Sulaiman,; Nur Hanie Mohd Latiff, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Wastewater contamination is one of the critical environmental issues that is becoming worse daily due to the development of human activities mainly produced from domestic, heavy metals, oil, agricultural, and industrial waste. From the Islamic perspective, Muslims play essential roles as khalifah on earth responsible for taking care of and preserving the balanced relationship between man and the environment. As such, phytotechnology, which applies plants and associated microorganisms-based technologies, has been emerging to examine the problems and provide sustainable solutions for this issue. In the 1980’s, the concept of phytoremediation was bornwhen the ability of plant species to accumulate high amounts of heavy metals in their tissue and organs was proved. There are several advantages of using aquatic plants for the remediation process, such as being very cost-effective, eco-friendly and safe. Selecting suitable aquatic plant species helps safely remediate the wastewater contamination without producing any toxic substances. This article summarises recent facts on phytoremediation by using aquatic plants as the best approach to remediate wastewater contaminants. Furthermore, some sustainability principles have been highlighted in the Quran and Sunnah, which can guide stakeholders and serve as a basis for any institution to introduce better environmental conservation and management policies through Islamic perspectives, particularly in the practice of phytoremediation for wastewater management.